Lymphoepithelioma-like carcinoma of the cervix-diagnostics, treatment, monitoring - Šipka, Aleksandar; Mandić, Aljoša; Stanulović, Nevena; Gutić, Bojana; Vasiljević, Tijana (Archive of Oncology, 2024)
Lymphoepithelioma-like carcinoma of the cervix (LELC) is a rare subtype of squamous cell carcinoma. This is a case report of a 40-year-old female patient diagnosed with LELC. The tumor is clinically presented as an exophytic mass on the front lip of the cervix. Magnetic resonance imaging (MRI) of the pelvis revealed a cervical tumor mass with a diameter of 21 mm. The findings of the preoperative pathohistological analysis of the biopsy tissue indicated LELC. The disease was clinically and radiologically staged as IB1 stage according to the 2009 FIGO classification, and the patient underwent surgical treatment. A total radical hysterectomy with pelvic lymphadenectomy was performed, followed by external beam radiotherapy. The patient was regularly monitored oncologically with the last check-up on February 2024 (36 months) and control MRI of the pelvis and abdomen without signs of recurrence of the underlying disease. The patient is in good general condition, without subjective complaints and side effects of the applied therapy. Key words: lymphoepithelioma-like carcinoma of the cervix, LELC, cervical carcinoma, radical hysterectomy.